THE ROLE OF DOG POPULATION MANAGEMENT IN ERADICATION OF RABIES: CASE STUDY IN PEJENG VILLAGE, TAMPAKSIRING DISTRICT, GIANYAR REGENCY, BALI PROVINCE - Sindawati, Kadek Ari; Puja, I Ketut; Dharmawan, I Nyoman Sadra (Buletin Veteriner Udayana, 2021)
Since 2008, rabies is still endemic in Bali. Dog Population Management is an effort to stabilize the dog population consisting of six components: education, legislation, identification and registration, vaccination, sterilization, and waste management in eradicating rabies. This program was implemented in Pejeng Village, Tampaksiring District, Gianyar Regency, Bali Province in November 2016, funded by Food and Agriculture Organization. This study aims to determine changes in knowledge, attitudes and ways of raising dogs in the community in the village of Pejeng after the application of Dog Population Management. This observational study uses a cross-sectional study through observation and dissemination of questionnaires directly to the field. The sampling technique uses probability sampling, a proportional stratified sampling technique with the number of samples was 313 respondents. It was conducted in November 2016 (before the Dog Population Management was implemented) and in September 2018 after the Dog Population Management was applied). The collected data were analyzed descriptively. The results before and after the application of Dog Population Management were analyzed by non-parametric analysis using the Wilcoxon test. Based on the results of this study, it was concluded that the Application of Dog Population Management significantly (P<0,05) could change knowledge, attitudes and ways of raising dogs in the community in Pejeng Village better than before.